Recognizing the inherent variability in dipteran colonization and decomposition rates of human donors in Sydney, Australia / Angela D. Skopyk, Shari L. Forbes and Hélène N. LeBlanc - Skopyk, Angela D.; Forbes, Shari L.; LeBlanc, Hélène N. (Faculty of Medicine, 2021)
Introduction: Human decomposition is influenced by intrinsic and extrinsic factors including entomological activity, which can result in variability in the decomposition process. In death investigations, forensic entomology, the study of insects in a legal context, is the preferred method to estimate a post-mortem interval after pathologist methods are no longer applicable. The purpose of the current study was to document the primary dipteran colonization and rates of decay during the decomposition processes of human donors with known causes of death. Methods: Five consenting human donors were placed in a forested area at the Australian Facility for Taphonomic Experimental Research (AFTER) in Sydney, Australia, and allowed to decompose in a natural environment. Temperature and humidity were monitored hourly while other factors like colonizers and decomposition stage were recorded at each visit to the site. Thermal summation, called Accumulated Degree-Days (ADD), was calculated to compare the rates of decay. Results: Results show that no two donors followed the same rate of decomposition. There were instances of delayed dipteran colonization, which resulted in slowed decomposition rates. Differences in rates of decay between donors could also have been influenced by intrinsic factors such as size, clothing and peri-mortem treatments. Conclusions: This research supports the larger body of research involving the precolonization interval of insects, emphasizing the numerous variables that can affect colonization. Further research into the pre-colonization interval, and factors that affect it, should be performed using human donors to better understand how this knowledge can be applied to death investigations.